Pengaruh Ukuran Perusahaan dan Debt to Equity Ratio terhadap Profitabilitas pada Perusahaan Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Girsang, Elysia Fianni; Rahmi, Namira Ufrida; Nasution, M. Irsan (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study aims to examine and analyze the impact of Company Size and Debt to Equity Ratio on Profitability in food and beverage companies listed on the Indonesia Stock Exchange during the 2021-2023 period. The population consists of 30 companies, and the sample includes 20 companies. Partial statistical tests show that the significance value of company size is 0.005<0.05, meaning Ha is accepted and Ho is rejected, which indicates that company size has a partial effect on profitability. Similarly, the significance value for the Debt to Equity Ratio (DER) is 0.025<0.05, meaning DER has a simultaneous effect on profitability. The results of the F-test show a significance value of 0.005<0.05, indicating that, simultaneously, company size and DER affect profitability in food and beverage companies listed on the IDX during the 2021-2023 period. The coefficient of determination test shows a value of 0.140, meaning that 14% of profitability can be influenced by company size and debt to equity ratio, while the remaining 86% is influenced by other variables outside the scope of this study.